LEARNING ORGANIZATION AS RESPONSIVE BEHAVIOR TOWARD THE POLICIES OF HIGHER EDUCATION QUALITY IMPROVEMENT - Hanafiah Hanafiah; Hendi S Muchtar (Journal Of Educational Experts (JEE), 2019)
The development of higher education quality becomes primary activities that are not negotiable. Various government policies on the development of higher education continue to be issued, such as the Laws of Higher Education, Quality Assurance System of Higher Education, and the National Standards for Higher Education. One of responsive behavior to the development of quality higher education that is the Learning Organization. Through learning organization, every policies relating to the development have been discussed formally as well as becoming the means of improving the capacity of human resources in higher education adaptively and generatively. Learning organization originated from the culture of individual and team learning. This has led to shape the betterment of the quality of higher education, and also in responding to the policies of the development of quality higher education. The authors propose the alternative tools for that matter, that is the fifth disciplines of learning organization from Peter Senge, et al., namely: (1) Systems Thinking, (2) Personal Mastery; (3) Mental Models; (4) Shared Vision; and (5) Team Learning. Approach of Learning Organization in response to the policy of the development of quality higher education is done through internal dynamics, analysis of daily problems, self renewal capacity, building competitiveness in a cooperative and, build healthy higher education in the midst of rapid environmental changes, complex, and dynamic.